Reflexão sobre políticas públicas e gestão de acervos em instituições de memória em Portugal - Graça Filipe; Conceição Serôdio; Leonor Calvão Borges; Ana Margarida Dias da Silva (Midas: Museus e Estudos Interdisciplinares)
This article, prompted by the sharing of knowledge and experiences of the authors, aims to contribute to a reflection on issues surrounding the policies of incorporation and disincorporation of memory institutions (archives, libraries and museums), especially in a context in which their functioning seeks to adapt to structural problems aggravated by the covid-19 pandemic. As the management of memory poses to all the institutions that promote it the problem of its relationship with forgetfulness, inseparable components in all societies and cultures, and recognizing that not all processes of incorporation of cultural goods are irreversible, our reflection encompasses this issue and intends to highlight the need for sustainable collection development policies. Based on legislation and with reference to scientific and academic bibliography and studies on the subject, the authors seek to problematize: the issue of managing collections and archives in each one of the memory institutions; the differences and similarities between them; and the positioning of each one in relation to communication in a digital environment. It is concluded that deaccessioning, an inverse process to accessioning, may be a necessary procedure and that the two are complementary, in a strategic and programmatic plan of the institutions. But the issue is far from generating consensus and it has been shown that it requires deep reflection and scientific debate, both in the professional field, which tends to be more subject to direct confrontation with crisis situations, and in the academic sphere, perhaps with greater critical and prospective margins.